2013
DOI: 10.1152/ajplung.00090.2013
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end-products supports lung tissue biomechanics

Abstract: The receptor for advanced glycation end-products (RAGE) and its soluble forms are predominantly expressed in lung but its physiological importance in this organ is not yet fully understood. Since RAGE acts as a cell adhesion molecule, we postulated its physiological importance in the respiratory mechanics. Respiratory function in a buffer-perfused isolated lung system and biochemical parameters of the lung were studied in young, adult, and old RAGE knockout (RAGE-KO) mice and wild-type (WT) mice. Lungs from RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…In their study, lungs of RAGE -/- mice showed a decreased expiratory airflow and increased lung compliance as compared to WT mice. However, they could only define an impact of RAGE on the respiratory function in mice from an age of five months, whereas we could detect an influence even in younger mice [36]. Sambamurthy et al observed comparable enlargement of alveolar dimensions in native RAGE -/- mice [37].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In their study, lungs of RAGE -/- mice showed a decreased expiratory airflow and increased lung compliance as compared to WT mice. However, they could only define an impact of RAGE on the respiratory function in mice from an age of five months, whereas we could detect an influence even in younger mice [36]. Sambamurthy et al observed comparable enlargement of alveolar dimensions in native RAGE -/- mice [37].…”
Section: Discussionmentioning
confidence: 72%
“…The RAGE-dependent differences in lung function and structure could be caused by insufficient cell-cell- and cell-matrix contacts. RAGE mediates interactions between two adjacent cells and enhances the adherence of alveolar epithelial cells to the basal membrane [2, 36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this observation, Quiesser et al suggested an important function of RAGE in cellular adhesion and spreading to the basal membrane, playing a structural role in the maintenance of the alveolar epithelium [32]. It has also been demonstrated that RAGE stimulates elastin expression and plays a supporting role in respiratory mechanics [48]. Furthermore, RAGE may belong to a family of cell adhesion molecules [49], making links with basal lamina components such as type IV collagen or laminin [28, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Robaiy et al elucidate the importance of the high RAGE expression in supporting the respiratory mechanics of the lung. Lungs from RAGE knockout (RAGE −/− ) mice show a significant increase in dynamic lung compliance and a decrease in the maximal expiratory air flow [176]. It is discussed that the biomechanically interaction of cells and their matrix, as well as the mechanically coupling of cells are affected.…”
Section: Physiological Role Of Ragementioning
confidence: 99%